Bibliometric analysis of research on COVID-19 by institutions located in Peru, 2020-2022 - Roque-Henriquez, Joel Christian (2024)
Objetive: Characterize the scientific production on COVID-19 by institutions located in Peru, period 2020-2022. Materials and methods: The study covered two databases (MEDLINE and Scopus). Original articles were included in which there was at least one researcher affiliated with an institution located in Peru, articles were excluded: i) in which there was no term about the pathology or viral agent in the title or objective of the study, ii) preprint. For the characterization, indicators of production, visibility and impact, and collaboration were used. Results: 1066 articles were analyzed. A growing scientific production was evidenced from 2020 to 2022. The top three topic areas were pandemic, mental health, and mortality. Two hundred seven (19.4%) articles were published in the United States journals and 185 (17.4%) in United Kingdom journals. The San Ignacio de Loyola University was the most productive institution with 161 (15.1%) articles. The co-authorship network between the institutions located in Peru is mostly made up and led by universities. The United States was the main country with which co-authorship was shared, Colombia in second place. Conclusions: One of the most researched subject areas was mental health; United States and United Kingdom journals ranked first and second in number of articles. The co-authorship network between the institutions located in Peru is mostly made up and led by universities. The United States and Colombia are the countries with which Peru shares the most co-authorships.